1982
DOI: 10.1073/pnas.79.14.4442
|View full text |Cite
|
Sign up to set email alerts
|

Cystine accumulation and loss in normal, heterozygous, and cystinotic fibroblasts.

Abstract: Medical SciencesCystine accumulation and loss in normal, heterozygous, and cystinotic fibroblasts (nephropathic cystinosis/amino acid storage/lysosomes)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Cystinotic fibroblasts appear metabolically normal with the exception of the inability to transport cystine from lysosomes, which results from a defective lysosomal transport system for cystine (13,14). This defect is specific for cystine; no other aminoacid, including Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cystinotic fibroblasts appear metabolically normal with the exception of the inability to transport cystine from lysosomes, which results from a defective lysosomal transport system for cystine (13,14). This defect is specific for cystine; no other aminoacid, including Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cystinosis is an autosomal recessive dis ease characterized by the excessive accumu lation of cystine in the lysosomes as a result of a defective cystine efflux [1][2][3][4][5]. Accumu lation of cystine occurs in almost all cells of the body but the kidney is the most vulnera ble organ [6].…”
Section: Introductionmentioning
confidence: 99%
“…concentrations of the relatively im permeable amino acid cystine into noncystinotic cells has limited initial investigations into the pathogenesis of the disease. This drawback was overcome in recent years when it was demonstrated that incubation of cells with the permeable methyl ester deriva tives of different amino acids leads to accu mulation of the respective amino acid in the lysosome [7], The lysosomal loading is due to the activity of intralysosomal esterases which cleave the methyl ester leaving high concentration of the less permeable free amino acid in the lysosomes [1][2][3][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Cystine was measured by the competitive binding assay (20). * Sample was obtained 5 hr after a dose of oral cysteamine.…”
mentioning
confidence: 99%